Environmental Degradation in Indian Ocean - Rafique, Muhammad Umair; Shah, Sayed Amir Hussain (Progressive Research Journal of Arts & Humanities (PRJAH), 2020)
Indian Ocean is the third largest ocean in the world spanning over an area of 73,556,000 Square. kilometers, that covers three continents, Africa, Asia, and Australia. Pakistan is an emerging strategic and geopolitical significant state of the South Asia; it has 1046 kilometers of coastline across the Arabian Sea, a region of Northern Indian Ocean. The country’s largest province ‘Baluchistan’ possesses 800 kilometers of coastline, whereas remaining 246 kilometers is in ‘Sindh’ province. The level of marine pollution is extremely high in Karachi, an economic hub and populous port city of the Sindh. The Karachi Port harbour area is full of toxic pollutants until they are evaporated or settle down at the bottom. The objective of this paper is to highlight the dilemma of marine pollution in Pakistan’s coastline especially in the port city of Karachi. The study is aimed to provide remedial measures to preserve endanger rare marine species of Pakistan’s territorial waters. The paper will also provide an empirical and theoretical overview of coastal governance in Pakistan.